IDNLearn.com provides a comprehensive platform for finding accurate answers. Discover reliable and timely information on any topic from our network of experienced professionals.
Answer:
Step-by-step explanation:
Are you certain you wrote the question accurately?—because none of the choices is correct.
rearrange 3x+y =-5 to solve for y:
y = -3x-5
substitute -3x-5 for y into the second equation:
12x + 3y = 13
12x + 3(-3x-5) = 13
12x - 9x - 15 = 13
3x = 28
x = 28/3
y = -3x-5 = -33
solution: (28/3, -33)